2019
DOI: 10.1128/iai.00100-19
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Typhimurium Interacts with CD209 Receptors To Promote Host Dissemination and Infection

Abstract: Salmonella enterica serovar Typhimurium, a Gram-negative bacterium, can cause infectious diseases ranging from gastroenteritis to systemic dissemination and infection. However, the molecular mechanisms underlying this bacterial dissemination have yet to be elucidated. A study indicated that using the lipopolysaccharide (LPS) core as a ligand, S. Typhimurium was able to bind human dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (hCD209a), an HIV receptor that promotes viral dissem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 53 publications
1
48
1
Order By: Relevance
“…It is well-documented that the surfaces of most parasites are highly glycosylated (11,27,29,76). Further investigations need to be done to determine corresponding parasite ligands, as we did in identification of the carbohydrate LPS core from many Gram-negative bacteria (29,30,38,40,56,59); as well as immune responses elicited by the T. gondii. Moreover, HIV uses gp120-DCSIGN interaction to initiate capture by DCs and transmission to CD4+ T cells (19).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It is well-documented that the surfaces of most parasites are highly glycosylated (11,27,29,76). Further investigations need to be done to determine corresponding parasite ligands, as we did in identification of the carbohydrate LPS core from many Gram-negative bacteria (29,30,38,40,56,59); as well as immune responses elicited by the T. gondii. Moreover, HIV uses gp120-DCSIGN interaction to initiate capture by DCs and transmission to CD4+ T cells (19).…”
Section: Discussionmentioning
confidence: 90%
“…Previous results, including some of our work, showed that APCs such as macrophages and dendritic cells (DCs) express CD209 receptors on their surface and have been shown to interact with pathogens that target CD209s for invasion (22,24,25,28,34,36,(54)(55)(56). To determine whether T. gondii can interact with mouse macrophages more readily, we examined the ability of T. gondii to invade peritoneal macrophages that express CD209 (57,58) compared to a macrophage cell line (RAW 264.7) that lacks the expression of CD209 receptors on its surface (59). Figure 1 and Figure S1 show invasion of GFP-labeled T. gondii into peritoneal macrophages and there's a cluster of parasites in some of the adherent cells, compared to that in RAW 264.7 cells.…”
Section: Toxoplasma Gondii Invades Mouse Peritoneal Macrophages More mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that several Gram-negative bacteria, including Salmonella Typhimurium (S. Typhimurium), Yersinia pseudotuberculosis (Y. pseudotuberculosis) and Yersinia pestis (Y. pestis), are able to interact with DC-SIGN (CD209s), a Ctype lectin and an innate immune receptor expressed by APCs, to hijack the APCs for host dissemination and infection (He et al, 2019;Yang et al, 2019;Ye et al, 2019). These studies were informed by the mechanism of HIV infection of APCs.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies show that N-acetylglucosamine (GlcNAc) sugar residues within the LPS core of several Gram-negative bacteria are exposed by loss of O-antigen, which helps in the targeting of CD209s by these pathogens (Zhang et al, 2006). The host dissemination and infection of some pathogens can be significantly reduced by inhibition of such receptor-ligand interactions with an oligosaccharide or its analogs (He et al, 2019;Yang et al, 2019;Ye et al, 2019), indicating that inhibition of LPS core-CD209s interaction may serve as a treatment or prevention strategy of infections caused by these pathogens.…”
Section: Introductionmentioning
confidence: 99%